2021
DOI: 10.3389/fimmu.2021.618737
|View full text |Cite
|
Sign up to set email alerts
|

Combined Immunotherapy With Belatacept and BTLA Overexpression Attenuates Acute Rejection Following Kidney Transplantation

Abstract: BackgroundCostimulatory blockade provides new therapeutic opportunities for ensuring the long-term survival of kidney grafts. The adoption of the novel immunosuppressant Belatacept has been limited, partly due to concerns regarding higher rates and grades of acute rejection in clinical trials. In this study, we hypothesized that a combined therapy, Belatacept combined with BTLA overexpression, may effectively attenuate acute rejection after kidney transplantation.Materials and MethodsThe rat kidney transplanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 52 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…50 Th1 cells can drive the proliferation of activated CD4 + and CD8 + effector T cells and enhance the cytotoxicity of natural killer cells by secreting inflammatory cytokines IL-2 and IFN-γ. 51,52 Th2 cells secreting IL-4 and IL-10 are involved in the induction of immune tolerance. 29,51 Studies have shown that the content of cytokine can also significantly affect the expression of PD-1/PD-L1 53 and regulate the therapeutic effect of immunosuppressive drugs in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…50 Th1 cells can drive the proliferation of activated CD4 + and CD8 + effector T cells and enhance the cytotoxicity of natural killer cells by secreting inflammatory cytokines IL-2 and IFN-γ. 51,52 Th2 cells secreting IL-4 and IL-10 are involved in the induction of immune tolerance. 29,51 Studies have shown that the content of cytokine can also significantly affect the expression of PD-1/PD-L1 53 and regulate the therapeutic effect of immunosuppressive drugs in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The activation and differentiation of T cells depend on the selection of costimulatory molecules and the composition of cytokines in the environment ( 74 ). On the one hand, cytokines secreted by Th1 cells, such as IFN-γ, TNF-α, and IL-2, can adversely affect the graft by recruiting and activating effector T cells ( 16 , 17 , 75 ). On the other hand, immunomodulatory cytokines secreted by Th2 cells, such as IL-4 and IL-10, can induce tolerance to liver allografts ( 16 , 39 , 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, cytokines secreted by Th1 cells, such as IFN-γ, TNF-α, and IL-2, can adversely affect the graft by recruiting and activating effector T cells ( 16 , 17 , 75 ). On the other hand, immunomodulatory cytokines secreted by Th2 cells, such as IL-4 and IL-10, can induce tolerance to liver allografts ( 16 , 39 , 76 ). Our results showed that TNF-α, IFN-γ, and IL-2 increased in allograft recipients, while IL-4 decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidney transplantation (KTx) is the most effective treatment for end-stage renal disease (1 , 2 ). The development of immunosuppressant therapies has greatly improved organ and recipient survival (3)(4)(5). However, acute rejection (AR) and delayed graft function (DGF) remain treatment obstacles that impair KTx outcomes, especially in the current era of donation after circulatory death (DCD) (6,7).…”
Section: Introductionmentioning
confidence: 99%